2013
DOI: 10.5402/2013/204560
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CYP2D6 Allele Frequencies and Identification of Novel SNPs and Sequence Variations in Sardinians

Abstract: e CYP2D6 enzyme is involved in the metabolism of many commonly prescribed drugs. e presence of polymorphisms in the CYP2D6 gene may modulate the enzyme level and activity affecting individual responses, to pharmacological treatment in drug level, response and adverse reactions. Aims. is study aimed to analyze the determination of allele frequencies in Sardinians and the comparison to frequencies found in the Caucasian Population. Methods and Materials. We used a Long PCR strategy coupled to direct genomic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The 69 polymorphisms analyzed in this study were selected using principal SNP web databases such as the Human CYP Allele Nomenclature Committee [7] and the NCBI Single Nucleotide Polymorphism dbSNP [8] websites. Selection criteria depended mainly on the pharmacogenetic effects described for every allele in the Caucasian population [5,7,[9][10][11][12][13][14][15][16]. Not all selected SNPs are involved in aminoacidic or transcriptional variation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 69 polymorphisms analyzed in this study were selected using principal SNP web databases such as the Human CYP Allele Nomenclature Committee [7] and the NCBI Single Nucleotide Polymorphism dbSNP [8] websites. Selection criteria depended mainly on the pharmacogenetic effects described for every allele in the Caucasian population [5,7,[9][10][11][12][13][14][15][16]. Not all selected SNPs are involved in aminoacidic or transcriptional variation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The 5 10-mer tag was added to PCR primers, in order to improve PCR efficiency. Name 5 10-mer tag 5 -Sequence-3 Direction From -1780 to -1758 P-1780 [5 [5]. Forward primer (P-1780, Table 2) was designed in a highly nonhomologous CYP2D6/CYP2D7P/CYP2D8P 5 untranslated region [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, because it was reported that there are differences in allelic distributions in populations of different ethnic group and geographic areas [30, 31], we first determined the CYP2C9 , CYP2C19, and CYP2D6 genotype profile of our 100 individuals from Salento, a Southern Italy region. A total of 12 different variant alleles were identified in the study population.…”
Section: Discussionmentioning
confidence: 99%